2020
DOI: 10.1097/md.0000000000021394
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exercise intervention for patients undergoing hemodialysis on fatigue and quality of life

Abstract: Background: This study aims to determine the therapeutic efficacy of exercise interventions for patients undergoing hemodialysis (HD) on fatigue and health-related quality of life (HRQoL). Methods: This review will only include randomized controlled trials (RCTs). The search strategy will be performed in 4 English databases, 4 Chinese databases, Clinical Trials.gov, and the Chinese Clinical Trial Registry. All English or Chinese RCTs, published from inception to May 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“… Functional Independence Measure (FIM) ( Matsufuji et al, 2015 ) Physical; Psychological; Social 6 Self-Care; Sphincter control; mobility; locomotion; communication; social cognition 18 Used to assess and grade a person's functional status based on the level of assistance he or she requires. FIM scores range from: 1–7, where 1 = Total dependence, and 7 = complete independence with no helper Piper Fatigue Scale (PFS) ( Zhang et al, 2020 , Reeve et al, 2012 ) Phycological; Physical; Social 4 Behavior; affect; sensory; cognitive/mood 27 22 items, each scaled using 0–10 to measure four dimensions of subjective fatigue. In addition to 5 writing questions that help to describe reasons and states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Functional Independence Measure (FIM) ( Matsufuji et al, 2015 ) Physical; Psychological; Social 6 Self-Care; Sphincter control; mobility; locomotion; communication; social cognition 18 Used to assess and grade a person's functional status based on the level of assistance he or she requires. FIM scores range from: 1–7, where 1 = Total dependence, and 7 = complete independence with no helper Piper Fatigue Scale (PFS) ( Zhang et al, 2020 , Reeve et al, 2012 ) Phycological; Physical; Social 4 Behavior; affect; sensory; cognitive/mood 27 22 items, each scaled using 0–10 to measure four dimensions of subjective fatigue. In addition to 5 writing questions that help to describe reasons and states.…”
Section: Resultsmentioning
confidence: 99%
“… Physical Zhang et al. (2020) ( Zhang et al, 2020 ) Systematic Review and meta -analysis Evaluation of the therapeutic efficacy of exercise for patients undergoing hemodialysis on fatigue and HRQoL. Patients with ESRD undergoing hemodialysis Inclusion Criteria: Patients with ESRD undergoing hemodialysis who were diagnosed using the Kidney Disease Improving Global Outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 To date, clinical trials have demonstrated that Baduanjin, Pilates, yoga, aerobic exercise, muscle relaxation exercise, resistance exercise, and aerobic-resistance combined exercise could improve the symptoms of fatigue in MHD patients, [15][16][17][18][19] and increase dialysis adequacy and urea clearance, 20 but are limited by sample size, lack of a control group, or short intervention duration, and the optimal exercise type and format for MHD patients remains uncertain. Several systematic reviews and meta-analyses have shown that exercise intervention could alleviate fatigue symptoms in MHD patients, [21][22][23][24] but only one specific type and time of exercise (intradialytic or interdialytic) are discussed; in addition, traditional meta-analysis cannot rank for different interventions. Meanwhile, network meta-analysis (NMA), also known as mixed treatment comparison or multiple treatments comparison meta-analysis, is a statistical method to directly and indirectly compare the effects of two or more treatments and allows the ranking of different treatments.…”
Section: What Is Knownmentioning
confidence: 99%
“…Recently, Zhang et al . [ 68 ] conducted a meta-analysis to define a protocol for systematic review and meta-analysis of the literature to study the therapeutic efficacy of exercise interventions for patients undergoing HD on fatigue and health-related QoL that could contribute to limit the bias due to heterogeneity of exercise protocols and outcomes.…”
Section: Effects Of Exercise On Skeletal Muscle Mass and Functionmentioning
confidence: 99%